2013
DOI: 10.1016/j.scaman.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The construction and controlling effect of a moral brand

Abstract: This paper explores the control effect of a moral brand through its brand culture. The moral brand culture distinguishes itself from other brand cultures by drawing on external claims for legitimacy. In this case, the brand drew upon a strong brand community, moral narratives in society, and the participative engagement with its values by many employees. As a consequence of these multiple and often external means of brand creation, managers were able to distance themselves from the process of brand and cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 61 publications
2
39
0
Order By: Relevance
“…4, 6). This form of corporate exploitation has been described in terms of the appropriation of the free labour of consumers, employees and communities (Arvidsson, 2005(Arvidsson, , 2014Caruana and Crane, 2008;Cova and Dalli, 2009;Land and Taylor, 2010) and in terms of the intensification of the managerial control over organizational culture (Endrissat et al, 2017;Kärreman and Rylander, 2008) and corporate ethics (Jeanes, 2013;Mumby, 2016). Recent work by Arvidsson (2007) and Mumby (2016) has suggested that ethics itself plays an important role in this process of subsumption in the creation of 'ethical capital' and an 'ethical surplus' that can be exploited by means of branding.…”
Section: Mediation and The Ethics Of Ambivalence In Brandingmentioning
confidence: 99%
See 2 more Smart Citations
“…4, 6). This form of corporate exploitation has been described in terms of the appropriation of the free labour of consumers, employees and communities (Arvidsson, 2005(Arvidsson, , 2014Caruana and Crane, 2008;Cova and Dalli, 2009;Land and Taylor, 2010) and in terms of the intensification of the managerial control over organizational culture (Endrissat et al, 2017;Kärreman and Rylander, 2008) and corporate ethics (Jeanes, 2013;Mumby, 2016). Recent work by Arvidsson (2007) and Mumby (2016) has suggested that ethics itself plays an important role in this process of subsumption in the creation of 'ethical capital' and an 'ethical surplus' that can be exploited by means of branding.…”
Section: Mediation and The Ethics Of Ambivalence In Brandingmentioning
confidence: 99%
“…In recent years, there has been a growing interest in the ethics of branding (Arvidsson, 2007(Arvidsson, , 2014Egan-Wyer et al, 2014;Jeanes, 2013;Klein, 1999). Muhr and Rehn (2014) have highlighted how companies use the narratives of human rights activists in the branding and selling of their products.…”
Section: Mediation and The Ethics Of Ambivalence In Brandingmentioning
confidence: 99%
See 1 more Smart Citation
“…The brand can attempt to paper over such contradictions by narrating a meaningful story about the job. The story is based on a moral story, which, to a large extent, is narrated outside of the work organization (Jeanes, 2013). Understanding brands as 'social identities' allows us to understand how employees construct their job as a meaningful activity that contributes to both the employees' and the consumers' lifestyles.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This leads us to the question of how a brand constructs meaningful 'social identities'. Existing research conducted by Jeanes (2013) has shown the important role that moral discourse plays in the process of branding. This article extends this research by revealing the specific 'modes' of identity work (Alvesson and Willmott, 2002) that are employed in the construction of a branded identity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%